2018
DOI: 10.2217/fon-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DQB1*03 and DRB1*07 Alleles Increase the Risk of Cervical Cancer Among Uighur and Han Women in Xinjiang, China

Abstract: This study suggests that HLA-DQB1*03 and DRB1*07 alleles may influence the immune response to HPV16 infection and increase the risk of CSCC among the Uighurs and Hans in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In turn, HLA DRB1*14, DRB1*16 and DQA1*0301 were more often observed in healthy "no CIN" women. Previous studies have described DRB1*15 association with cervical cancer in various populations [6][7][8][9]17,18]. We have found this allele significantly more often in CIN1 and CIN2+ patients.…”
Section: Discussionsupporting
confidence: 58%
“…In turn, HLA DRB1*14, DRB1*16 and DQA1*0301 were more often observed in healthy "no CIN" women. Previous studies have described DRB1*15 association with cervical cancer in various populations [6][7][8][9]17,18]. We have found this allele significantly more often in CIN1 and CIN2+ patients.…”
Section: Discussionsupporting
confidence: 58%
“…Associations of HLA-B*15, HLA-B*15:01, HLA-DRB1*11, HLA-DRB1*11:01, HLA-DRB1*13, HLA-DRB1*13:02, HLA-DRB1*15, HLA-DQB1*06:01, and HLA-DQB1*06:04 were not significant but were replicated with directional concordance of the allelic CC risk (eTable 1 in the Supplement ). 13 , 14 , 16 , 17 , 18 , 19 , 20 , 21 …”
Section: Resultsmentioning
confidence: 99%
“…11 On the other hand, the HLA alleles previously reported to have associations with CC did not reach the significant but were replicated with directional concordance of the allelic CC risk (eTable 1 in the Supplement). 13,14,[16][17][18][19][20][21] When conditioned on HLA-B*52:01, no other variants in the MHC region satisfied the genomewide significance (Figure 1B). This suggested that all the other variants that originally satisfied the At an amino acid level, the most significant association was observed at the amino acid position 171 of the HLA-B molecule (HLA-B p.Tyr171His; OR = 1.47; 95% CI, 1.30-1.66; P = 1.2 × 10 −9 ) (eTable 2 in the Supplement).…”
Section: Association Analysis and Conditioningmentioning
confidence: 96%
See 1 more Smart Citation
“…Worldwide in non-LS populations, different HLA alleles have been reported to be associated with various cancers, such as cervical [ 26 , 42 , 43 ], leukemia [ 44 ], hepatocellular [ 45 ], lung squamous cell [ 46 ], cutaneous T cell lymphoma [ 47 ], and gastric carcinomas [ 48 , 49 ]. For instance, the HLA-DP gene polymorphisms ( HLA-DPB1*03:01 and HLA-DPB1*13:01 ) have been significantly associated with an increased risk of cervical cancer in Chinese populations [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%